Hyperendemicity of Rift Valley fever in Southwestern Uganda associated with the rapidly evolving lineage C viruses - Bakamutumaho, B.; Juma, John; Clancey, E.; Nyakarahuka, L.; Situma, S.; Odinoh, R.; Dawa, J.; Nasimiyu, C.; Eskew, E.A.; Balinandi, S.; Mulei, S.; Kayiwa, J.; et al. (Oxford University Press, 2026)
Introduction: Recent Rift Valley fever (RVF) epidemiology in eastern Africa region is characterized by widening geographic range and increasing frequency of small disease clusters. Here we conducted studies in the southwestern (SW) Uganda region that has since 2016 reported increasing RVF activities.